Thermal tolerance evaluation and related microsatellite marker screening and identification in the large yellow croaker Larimichthys crocea - 陈小明 李佳凯 王志勇 蔡明夷 刘贤德 (Chinese journal of oceanology and limnology, 2017)
Thermal tolerance to high temperature was evaluated in the large yellow croaker Larimichthys crocea. The survival thermal maximum for L. crocea was 33.0℃, the 50% critical thermal maximum （50% CTMax） was 35.5℃, and the critical thermal maximum （CTMax） was 36.0℃. Three microsatellite markers （LYC0148, LYC0200 and LYC0435）, associated with thermal tolerance were screened and identified using a Bulked Segregation Analysis （BSA） method. These markers have six amplified fragments in which four are related to thermal tolerance. These fragments were cloned and sequenced, and the results showed the core motif were all ＂AC＂ repeats. For LYC0148 and LYC0200, the lengths of fragments are 18l bp and 197 bp, respectively. For LYC0435, which has two fragments, the fragment lengths are 112 bp and 100 bp. The results provide useful molecular markers for thermal-tolerance breeding of large yellow croaker in the near future.